Level of stress among schoolteachers of a school in South Delhi, India - Mamta Parashar; Deeksha Ellawadi; Mitasha Singh; Ram Chander Jiloha (Wolters Kluwer Medknow Publications, 2019)
Background: Modernization and increasing level of competition in day to day life has increased the expectations from teachers. Objective: To describe the level of stress and its associated factors among teachers using Teacher's stress inventory in a government school of urban area of South Delhi. Methods: A cross sectional study among teachers of a senior secondary school located in south Delhi. This was part of mental health literacy workshop conducted March 2017. 124 teachers attended the same and 94 participated in the study. Teachers' stress inventory scale was used as a tool to assess the level of stress along with demographic factors of the study participants. Only 82 completed questionnaires were included in analysis. Results: The mean score among discipline and motivation sub category was a significantly higher source of stress among young age teachers (P <0.001). The mean scores among females were higher as compared to males among the sources of stress however the difference was not statistically significant. Joint family was a significant stressor source especially under professional distress in bivariate analysis (P: 0.04). As the experience duration increased the mean stress score also increased (correlation coefficient: 0.10, P: 0.36). All the variables were subjected to multiple linear regression models and it was found that gender, education and family income are significant predictors with stress as dependent variable. Conclusion: The social and economic instability cut across all ages and increase the risk of stress and burnout.